A gramaticalização do item agora no português brasileiro - Elane Calmon Silva (2010)
This paper presents a review of item now from the perspective of grammaticalization. Through a diachronic study, quantitative, in two corpus: 1986 and 2006, both speakers of the city of Belo Horizonte.We studied the changes experienced by the linguistic constructions of the item now, that is, what steps are these changes and if there is a way to understand how these steps are processed.We confirm that item from a lexical function, as an adverb of time, evolves to the grammatical function as aversive articulator, the articulator conclusive, discourse marker, interjection and indicatoridiom.We use assumptions of the theory of variation and change that concern the role of analysis of the apparent time and real time in the description of language change and saw that the variation affects the innovation of an item, but realize that there are other factors besides those provided in thistheory that interfere with the construction of an innovative way.We saw that the second item now does not obey the expected trajectory in a prototypical study of grammaticalization, because now there is still an intensely and now competes with two other planners and discourse markers, specifically with the articulator but.